LGB Employees and their experiences of Fly in Fly Out (FIFO) employment in Western Australia - Bahtic, Mirsad; Fitzgerald, Scott; Burgess, John (Edward Elgar, 2022)
The ability to disclose sexuality at work was influenced by the level of organisational support and inclusive workplace cultures that discourage discriminatory behaviour. Due to the uniqueness of each FIFO employee, it is recommended that organisations strive to develop and adopt transformative policies and practices which recognise a range of minorities based not only on sexuality, but also age, ethnicity, and class if they wish to be inclusive and address inequality across the entirety of the organisation (Dickens, 2005). If organisations in the mining industry were to adopt formal support networks, such as LGB (lesbian, gay, bi sexual) group networks, they could potentially provide a voice for sexual minorities. Networks can act as a collective mechanism in which greater visibility and community for members can be established (Colgan & McKearney, 2012), and promote change in a positive manner. By bringing together sexual minority employees, networks can provide social support in the organisation (Colgan & McKearney, 2012), which has been positively linked to coping strategies and the management of various difficulties faced by these minorities (Willis, 2010). Essentially, a network offers employees an antidote to loneliness in the organisation, and a community where they can be open about their sexuality (Colgan & McKearney, 2012); however, some employees might avoid voicing their concerns as they believe it could lead to further mistreatment or they feel they will be looked at differently by other co-workers (McFadden & Crowley-Henry, 2017). As such, a more nuanced approach to LGB support in such mining organisations is necessary.